Ganadería, trasterminancia y trashumancia en los territorios vascos en el tránsito del medievo a la modernidad (siglos XV y XVI) - Aragón Ruano, Álvaro (Cuadernos de Historia Moderna, 2006)
The present article tries to bring new data on stockbreeding in the Basque territories during the Modern Age. First of all, it is about to break with false paradigms that have come repeating during long time, bringing unpublished data. The classics of the Basque historiography have always stressed the rural and agrarian character of the Basque economy; in spite of it, activities such as stockbreeding have never occupied a fundamental space as object of study among historians, who in many cases have accepted the theories of ethnographers and anthropologists without contrasting them. Stockbreeding in Basque lands followed Cantabrian models, which come being studied for some decades by the Galician, Asturian or Cantabrian historians; schools that have established new methodologies for the study of stockbreeding, the predominant livestocks, the exploitation regime, its economic impact, etc., and whose example has unfortunately not been followed in the Basque case.